Magnetic Resonance Imaging Features of Common Posterior Fossa Brain Tumors in Children: A Preliminary Vietnamese Study - Duc, Nguyen Minh (Open Access Maced J Med Sci, 2019)
BACKGROUND: Magnetic Resonance Imaging (MRI) nowadays plays an important role in the evaluation of posterior fossa brain tumours in children for appropriate diagnosis, treatment planning, and follow-up. AIM: To assess the MRI features of common posterior fossa brain tumours including medulloblastomas, ependymomas, and pilocytic astrocytomas along with the postoperative parameters to contribute the local knowledge to the neuroradiology and neurosurgery fields. METHODS: The study was performed at Children’s Hospital 02 from January 2016 to June 2019. In this study, all pediatric patients adopted MRI to evaluate the posterior fossa brain tumours’ characteristics and then underwent surgery to eradicate the posterior fossa tumours. We retrospectively compared the baseline parameters, MRI parameters, and postoperative parameters among medulloblastomas, ependymomas, and pilocytic astrocytomas. RESULTS: There were 62 patients (27 medulloblastomas, 20 ependymomas, and 15 pilocytic astrocytomas) in this research. The main structure of medulloblastomas and ependymomas was predominantly solid, whereas the main structure of pilocytic astrocytomas was superiorly cystic (p < 0.05). Ependymoma tended to extend tumour through foramina of Luschka and Magendie (p < 0.05). Medulloblastomas chiefly showed iso intensity on T2W and FLAIR images meanwhile ependymomas and pilocytic astrocytomas predominantly appeared hyperintensity on T2W and FLAIR images. Medulloblastomas and ependymomas were mostly high intensity on DWI, and low intensity on ADC whereas pilocytic astrocytomas were usually low intensity on DWI and high intensity on ADC. After injecting CE, pilocytic astrocytomas showed a mixed intensity whereas the signal intensity of medulloblastoma and ependymoma on T1CE was generally strong. There were positive correlations between FH diameter and estimated blood loss (r = 0.289, p < 0.05); and surgical time (r = 0.312, p < 0.05). CONCLUSION: MRI plays a crucial role in demonstrating the features of posterior fossa brain tumours for appropriate diagnosis of medulloblastomas, ependymomas, and pilocytic astrocytomas. Medulloblastomas are problematic tumours and the clinicians should also take into consideration in cases of larger feet-to-head diameter of tumours to ensure the efficacy and safety surgery for patients.